Ion Velocity and Temperature Variation Around Topside Nighttime Irregularities: Contrast Between Low‐ and Mid‐Latitude Regions. Issue 2 (2nd February 2021) - Park, Jaeheung; Heelis, Roderick; Chao, Chi Kuang
Abstract: Studies on low‐/mid‐latitude ionospheric irregularities have a long history, but ion temperature and drift velocity variations within the irregularities have been rarely investigated, especially at mid‐latitudes. To fill this knowledge gap, we statistically investigate ion temperature and velocity of mid‐latitude ionospheric irregularities and compare them to those of low‐latitude ones. This study mainly relies on in situ plasma moment data from the newly launched Ionospheric Connection Explorer (ICON) satellite and is supplemented by Republic of China Satellite 1 (ROCSAT‐1) data in 2000–2004. At low latitudes (|MLAT|<10°) plasma density irregularities encountered by ICON have the following properties: lower‐density regions have cooler ions and more poleward/westward/outward velocity than the ambient plasma, which agrees with previous reports on equatorial plasma bubbles. At mid‐latitudes (|MLAT| = 10°∼30°), the opposite trends are observed: lower‐density regions have hotter ions and more equatorward/eastward/inward drift than the ambient, which is a new finding in this study. The mid‐latitude observations can be put into the context of Medium‐Scale Traveling Ionospheric Disturbance (MSTID) properties reported previously, which evidences that topside irregularities at nighttime mid‐latitudes generally represent MSTIDs. ROCSAT‐1 data support the contrast between low‐ and mid‐latitude ionospheric irregularities. Key Points: For low‐latitude topside irregularities, lower‐density regions have cooler ions and more poleward/westward/outward drift than the ambient For mid‐latitude topside irregularities, lower‐density regions have hotter ions and more equatorward/eastward/inward drift than the ambient Both Ionospheric Connection Explorer and Republic of China Satellite 1 data support the contrast between low‐ and mid‐latitude irregularities